Al-Iqtishad : Jurnal Ilmu Ekonomi Syariah ( Journal of Islamic Economics) - Wiwiek Rabiatul Adawiyah (Fakultas Syariah dan Hukum UIN Syahida Jakarta, 2015)
The Impact of Financial Liberalization on Islamic Banks’s Efficiency in Indonesia Wiwiek Rabiatul Adawiyah 141-150 Effects of Service Quality, Customer Trust, and Customer Religious Commitment on Customer Satisfaction and Loyalty of Islamic Banks in East Java Rachmad Hidayat, Sabarudin Akhmad, Machmud 151-164 Peer Group Effects on Moslem Consumer’s Decision To Purchase Halal Labeled Cosmetics Muniaty Aisyah 165-180 The Intellectural Capital Effect on Financial Performances at Islamic Insurance Rizqon Halal Syah Aji & Kurniasih 181-196 Capital Market Integration: Palestine and Israeli Experience Tulus Suryanto & Abdul Razak Abdul Hadi 197-206 The Effect of Productive Zakah Mentoring on The Wealth of Mustahik Rizky Andriati & Nurul Huda 207-216 The Image of Financial Institution as Islamic Bank in Mediation Service Quality and Customer Satisfaction on Customer Loyalty in Purwokerto Chandra Warsito 217-228 Financial Ratio and Its Influence to Profitability in Islamic Banks Erika Amelia 229-240 Human Resources Development of Sharia Banking: Phenomenological Approach Burhanuddin Yusuf 241-250 Application of Pattern of Islamic State Revenue Policy to Improve The Ability of Indonesia’s Fiscal Any Setianingrum 251-261